RASA1/NF1 mutant lung cancer: Racing to the clinic? - Kitajima, Shunsuke (Clin Cancer Res, 2018)
Although mutation of NF1 has been described in non-small cell lung cancer (NSCLC), co-mutation with RASA1, another Ras-GTPase activating protein (RasGAP), defines a novel genetically defined subclass of NSCLC. RASA1/NF1 mutant cell lines are highly sensitive to MEK inhibitors, warranting clinical evaluation of MAPK inhibition in this subclass of patients.